2014
DOI: 10.3389/fpsyg.2014.00974
|View full text |Cite
|
Sign up to set email alerts
|

The joint Simon effect: a review and theoretical integration

Abstract: The social or joint Simon effect has been developed to investigate how and to what extent people mentally represent their own and other persons' action/task and how these cognitive representations influence an individual's own behavior when interacting with another person. Here, we provide a review of the available evidence and theoretical frameworks. Based on this review, we suggest a comprehensive theory that integrates aspects of earlier approaches–the Referential Coding Account. This account provides an al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
178
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(198 citation statements)
references
References 102 publications
18
178
2
Order By: Relevance
“…The latter result is in line with the referentialcoding account (Dolk et al, 2014;Dolk et al, 2013), and specifically with the intentional-weighting hypothesis (Memelink & Hommel, 2013). The pointing gesture did indeed increase the discrepancy between the compatible and incompatible conditions in the horizontal space.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The latter result is in line with the referentialcoding account (Dolk et al, 2014;Dolk et al, 2013), and specifically with the intentional-weighting hypothesis (Memelink & Hommel, 2013). The pointing gesture did indeed increase the discrepancy between the compatible and incompatible conditions in the horizontal space.…”
Section: Discussionsupporting
confidence: 77%
“…Moving from the aforementioned assumption, the referential-coding account (Dolk et al, 2014;Dolk et al, 2013) suggests that in the context of the JST, events can be coded as potential effects of an action, regardless of the specific source (e.g., a participant, a computer, or a metronome). Hence, each event produced beside a participant is able to trigger a conflict with the potential events produced by the participant him-or herself (Prinz, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies have observed the correspondence effect in a special version of this task, called the joint go-nogo task, in which two participants each perform a go-nogo task on complementary target features (e.g., Sebanz, Knoblich, & Prinz, 2003, 2005Sebanz, Knoblich, Prinz, & Wascher, 2006). Whereas some researchers have favored a social interpretation of the effect and hypothesized a tendency for people to co-represent other persons' actions (i.e., the action co-representation account; see Sebanz & Knoblich, 2009, for reviews), others have argued that any salient, spatial event, irrespective of whether it appears in a social context, could elicit the correspondence effect inasmuch as it provides a response reference (i.e., the referential coding account; see Dolk et al, 2014, for a review). Below, we briefly discuss those two different views.…”
Section: Introductionmentioning
confidence: 98%
“…In a set of recent theoretical approaches, namely Referential Coding and Theory of Event Coding (Dolk et al, 2014;Hommel et al, 2001), joint effects are attributed to the overlapping perceptual (stimulus) and motor (action) codes provided in the environment. These theories were mainly proposed to explain both social and non-social Simon effects, and they claim that contextual cues may influence the action representations due to the conflicting codes they provide, and this causes action selection difficulty.…”
Section: Joint Actions Attention and Cognitive Loadmentioning
confidence: 99%